![{ \sin}^{2} \alpha + { \sin}^{2}(120 - \alpha ) + { \sin}^{2}(120 + \alpha ) = \frac{3}{2 } \\ \\ prove \: it { \sin}^{2} \alpha + { \sin}^{2}(120 - \alpha ) + { \sin}^{2}(120 + \alpha ) = \frac{3}{2 } \\ \\ prove \: it](https://tex.z-dn.net/?f=+%7B+%5Csin%7D%5E%7B2%7D+%5Calpha++%2B++%7B+%5Csin%7D%5E%7B2%7D%28120+-++%5Calpha+%29+%2B++%7B+%5Csin%7D%5E%7B2%7D%28120+%2B++%5Calpha+%29+%3D++%5Cfrac%7B3%7D%7B2+%7D++%5C%5C++%5C%5C+prove+%5C%3A+it)
prove it
Answers
Sine and cosine \sin(\theta) = \cos(90^\circ-\theta)sin(θ)=cos(90
∘
−θ)sine, left parenthesis, theta, right parenthesis, equals, cosine, left parenthesis, 90, degree, minus, theta, right parenthesis
\cos(\theta) = \sin(90^\circ-\theta)cos(θ)=sin(90
∘
−θ)cosine, left parenthesis, theta, right parenthesis, equals, sine, left parenthesis, 90, degree, minus, theta, right parenthesis
Tangent and cotangent \tan(\theta) = \cot(90^\circ-\theta)tan(θ)=cot(90
∘
−θ)tangent, left parenthesis, theta, right parenthesis, equals, cotangent, left parenthesis, 90, degree, minus, theta, right parenthesis
\cot(\theta) = \tan(90^\circ-\theta)cot(θ)=tan(90
∘
−θ)cotangent, left parenthesis, theta, right parenthesis, equals, tangent, left parenthesis, 90, degree, minus, theta, right parenthesis
Secant and cosecant \sec(\theta) = \csc(90^\circ-\theta)sec(θ)=csc(90
∘
−θ)